The Influence of Marketing Mix on Coffee Consumer Satisfaction at Kopi Mane Coffeeshop - Anggita Vanesa Liunima; Fernando Saragih (CV. Era Digital Nusantara, 2026)
Indonesia is one of the world’s largest coffee producers, with high sales volumes and a wide variety of coffee types. However, despite this strong consumption, dissatisfaction remains in several aspects of processed coffee sales. This situation indicates the need for appropriate strategies to maintain consumer satisfaction. The high sales of coffee also reflect a positive interaction between supply and demand, demonstrating diverse consumer responses to coffee products as well as the factors influencing purchasing decisions. Based on this, the present study examines how the marketing mix influences consumer satisfaction in coffee purchases, specifically at Mane Coffee. A quantitative approach was employed using a survey method with 120 respondents obtained through incidental sampling. The research instrument consisted of 35 statements that passed validity and reliability tests. Data were analyzed using multiple linear regression, which was considered appropriate as the data met the requirements of the classical assumption test. The results revealed that the variables of product, price, place, and promotion have a positive and significant effect on consumer satisfaction, both partially and simultaneously. These findings highlight the crucial role of the marketing mix in enhancing consumer satisfaction within the coffee industry.